The effect of docosahexaenoic acid (DHA) supplementation on total antioxidant capacity (TAC), superoxide dismutase (SOD), and interleukin-6 levels in underweight pregnant women - Siahaan, Salmon Charles; Santoso, Budi; Ismayani, Kanti; Yuwono, Natalia; Md Aris, Mohd Aznan (Universitas Airlangga, 2024)
Objective: Underweight pregnant women face oxidative stress and inflammation, increasing their risk of intrauterine growth restriction (IUGR) and preterm birth. This study investigates the effects of DHA supplementation on Total Antioxidant Capacity (TAC), Superoxide Dismutase (SOD), and Interleukin-6 (IL-6) in underweight pregnant women, along with the correlation between DHA and these markers.